Ingestive behavior and temperament of Nellore cattle classified for residual feed intake - Aldrighi, Julian (2019)
The objective of this study was to evaluate the relationship between ingestive behavior, temperament and residual feed intake (RFI) in Nellore cattle. Sixty-two bulls and 56 heifers after weaning, housed in individual pens, were evaluated in individual performance tests. Animals were classified as low RFI ( 0.135 kg day-1; greater than mean plus 0.5 standard deviation). Ingestive behavior was evaluated for 24 h by direct observation, every 24 days in bulls or every 10 days in heifers. Temperament was assessed by flight speed, reactivity in mobile confinement, composite score, and serum cortisol measurement. The most efficient animals (low RFI, 5.6 kg DM day-1) consumed 7% less feed than animals with medium efficiency (mean RFI, 6.0 kg DM day-1) and 13% less than the least efficient animals (high RFI, 6.34 kg DM day-1). More feed efficient animals spent a longer time feeding and ruminating per kg of DM consumed. Similarly, more efficient animals consumed less DM per hour and ruminated less DM per hour, but made the same number of visits to the feed bunk. High-efficiency animals were 13% and 35% faster to walk 1.77 m after release from the scale than medium- and low-efficiency animals, respectively, suggesting a more reactive temperament without differences in reactivity, composite score, or serum cortisol. Feed efficiency is associated with ingestive behavior and temperament in Nellore cattle. More efficient animals consume and ruminate less feed over the same period of time than animals with medium and low feed efficiency. In addition, more efficient animals exhibit a faster flight speed and are more reactive than less efficient animals.